New Straits Times, 30 Mei 2008 - Sheila Sri Priya (The New Straits Times Press (M) Bhd, 2008)
Kampung Medan residents approached state assemblyman Haniza Mohamed Talha to highlight their problems with New Pantai Expressway (NPE) Sdn Bhd.